Incidence of deep venous thrombosis in patients with both Pulmonary Embolism and COPD - Castellana, Giorgio; Intiglietta, Pierluigi; Dragonieri, Silvano; Carratù, Pierluigi; Buonamico, Paolo; Peragine, Maria; Capozzolo, Alberto; Carone, Mauro; Carpagnano, Giovanna Elisiana; Resta, Onofrio (Acta Biomedica Atenei Parmensis, 2021)
BACKGROUND. There are no studies investigating populations of patients with both pulmonary embolism and chronic obstructive pulmonary disease (PE-COPD) with and without deep venous thrombosis (DVT).AIM OF THE STUDY. To define prevalence of DVT in COPD with PE and to compare characteristics of COPD patients who develop PE, with and without DVT. Secondly, we aimed to assess differences in the localization of PE among study groups. METHODS. 116 patients with PE were enrolled in a retrospective study. Clinical data as well as echocardiographic and lower limb ultrasonography records were collected for all subjects.Subjects were divided into two groups according to the presence of COPD: Group 1, 54 patients with diagnosis of PE without COPD and Group 2, 66 patients diagnosed of PE with  COPD. Then, individuals of Group 2 were subdivided in two subgroups according to the presence (n=21) or absence (n=45) of DVT.RESULTS. 33% of patients with COPD and PE showed DVT.  These subjects had higher PaCO2 and ejection fraction (p